2023
DOI: 10.3390/rs15030819
|View full text |Cite
|
Sign up to set email alerts
|

Risk Evaluation of the Sanalona Earthfill Dam Located in Mexico Using Satellite Geodesy Monitoring and Numerical Modeling

Abstract: Dams are essential structures in the growth of a region due to their ability to store large amounts of water and manage it for different social activities, mainly for human consumption. The study of the structural behavior of dams during their useful life is a fundamental factor for their safety. In terms of structural monitoring, classic terrestrial techniques are usually costly and require much time. Interferometric synthetic aperture radar (InSAR) technology through the persistent scatterer interferometry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Liu et al (2021) [16] used distributed scatterer InSAR (DS-InSAR) to monitor the Xiaolangdi project, and the monitoring results showed that the maximum deformation velocity of the Xiaolangdi Dam was −10.09 mm/year, which was cross-verified with the SBAS results, and the monitoring results showed a high level of consistency. Vazquez-Ontiveros et al (2023) [17] used PS-InSAR technology to monitor the crest structure of the Sanalona Dam and showed that InSAR could achieve accuracy similar to GPS. Xiao et al (2022) [18] used TS-InSAR technology to investigate the failure of the Sardoba Dam in Uzbekistan and found that there was a 60 mm settlement difference before the dam failure.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2021) [16] used distributed scatterer InSAR (DS-InSAR) to monitor the Xiaolangdi project, and the monitoring results showed that the maximum deformation velocity of the Xiaolangdi Dam was −10.09 mm/year, which was cross-verified with the SBAS results, and the monitoring results showed a high level of consistency. Vazquez-Ontiveros et al (2023) [17] used PS-InSAR technology to monitor the crest structure of the Sanalona Dam and showed that InSAR could achieve accuracy similar to GPS. Xiao et al (2022) [18] used TS-InSAR technology to investigate the failure of the Sardoba Dam in Uzbekistan and found that there was a 60 mm settlement difference before the dam failure.…”
Section: Introductionmentioning
confidence: 99%
“…For comprehensive research on dam displacement monitoring, various measurement techniques should be used [23].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, establishing dam structural safety is required to quantify the risk associated with a dam reservoir system. In other words, for the system's initial state and various failure modes, it is important to evaluate the risk of loading events as well as the system reaction for a given load condition [23].…”
Section: Introductionmentioning
confidence: 99%
“…Several scientific publications have reported on the successful application of PSInSAR technology in analyzing dam deformation. Wang et al (2011) used this technology to study the Three Gorges Dam area in China on the Yangtze River, while Vázquez-Ontiveros et al (2023) studied the Sanalona Dam in Mexico. The results obtained through PSInSAR were consistent with traditional geodetic methods and GNSS measurements.…”
Section: Page Layoutmentioning
confidence: 99%